Legal Force of Electronic Certificates (E-Certificates) Issued by The National Land Agency (BPN) as A Form Oo Land Rights Ownership - Rihesta, Dwi Adi Pangestika Putra; Fajar Riyanto, Taufan (TABELLIUS: Journal of Law, 2025)
Land certificates issued based on the Basic Agrarian Law (UUPA) have significant evidentiary power (as regulated in Article 19 paragraph (2) letter c). This means that the evidentiary power of the certificate is not absolute, but strong enough. On a scientific basis, the author is motivated to conduct a scientific study containing the Legal Power of Electronic Certificates (E-Certificates) Issued by the National Land Agency (BPN) as a Form of Land Ownership Rights. The research method that will be used in this research is a qualitative approach, namely a way or research method that emphasizes analysis or descriptive. Based on the research results, there are research results on the Legal Power of Electronic Certificates (E-Certificates) Issued by the National Land Agency (BPN) as a Form of Land Rights Ownership, namely the Legal Power of Electronic Certificates (E-Certificates) Issued by the National Land Agency (BPN), namely Electronic certificates with analog certificates have the same position as valid evidence and provide legal certainty for land rights holders in land registration in Indonesia. The implementation of this electronic certificate has not been implemented in the meeting of Commission II of the Indonesian House of Representatives and the Minister of ATR/BPN on the grounds of delaying the security of data listed on the electronic certificate and the regulations of the Minister of ATR/BPN have not regulated data security on digital land certificates as a form of weakness in the regulation, and the Security Guarantee of E-Certificates Issued by the National Land Agency (BPN) as a Form of Land Rights Ownership, namely the Issuance of e-Certificates by BPN brings many advantages in terms of security, efficiency, and transparency in the management of land rights in Indonesia. This secure and technology-based system provides assurance to the community that their land ownership rights are protected and clearly recorded in a legitimate system, reducing the potential for conflict and increasing ease in managing land rights.